Penerapan Model Pembelajaran Experiential Learning untuk Meningkatkan Hasil Belajar Siswa Kelas X Jurusan Teknik Pemesinan SMK Negeri 2 Kota Ternate pada Mata Pelajaran Prakarya dan Kewirausahaan - Sunarti Djoko; Umar Abdulhalim (Program Studi Pendidikan Ekonomi STKIP Kie Raha Ternate, 2023)
ABSTRACT This study aims to determine the increase in student learning outcomes after taking action using experiential learning models. This study uses a classroom action research approach. The research was conducted at SMKN 2 Ternate City, North Maluku Province. The population in this study were all 120 class X students of the Mechanical Engineering Department at SMKN 2 Kota Ternate. The sample in this study were students of SMKN 2 Kota Ternate class X of the Department of Mechanical Engineering, totaling 30 students, consisting of 29 male students and 1 female student. Based on the results of data analysis on pre-action the average score of 30 class X Mechanical Engineering students at SMK Negeri 2 Ternate City was 5.70 and only 2 students or 6.66% were declared passed or above the KKM score. Whereas in cycle II it was found that there were major changes after the experiential learning program was carried out where previously the KKM in the pre-action average pretest score only reached 50.7 in cycle II the post-test average value was 70.5.